Advancing Topological Interlocking Structures: Recent Developments, Applications, and Challenges in Civil Engineering - Maliheh Tavoosi Gazkoh; Xiaoshan Lin; Annan Zhou (International Journal of Concrete Structures and Materials)
Abstract Topological interlocking structures have garnered significant attention for their distinctive properties, including robust resistance to crack propagation, outstanding energy absorption, adaptable flexibility, high resistance to missing elements and easy assembly and disassembly. Moreover, integrating various materials into a single structure enables versatile design possibilities. This paper comprehensively reviews recent research on topological interlocking elements and structures, encompassing element designs, manufacturing techniques and engineering applications. Furthermore, it explores the performance of topological interlocking structures, covering aspects such as fracture resistance, structural integrity, bending flexibility, ease of assembly and disassembly and energy absorption. While topological interlocking elements offer various benefits, challenges remain in their broader implementation, particularly as structural members in civil engineering structures. This paper engages in a critical discussion of existing research gaps and outlines directions for future research.